Investors’ Perceptions of Investment Decisions in the Stock Market: A Study of Pokhara Valley - Ranabhat, Deepesh; Ojha, Deepak; Adhikari, Prameshwor; Lamichhane, Keshav; Koirala, Sandeep (Kshitiz Management Review, 2026)
This study analyses the factors influencing investors’ perception of investment decisions in the stock market within the context of Pokhara Valley, Nepal. The study uses a descriptive research design in which 200 investors were selected as the sample. Primary data were collected through structured questionnaires and interviews. Regression analysis was conducted to examine the effect of various independent variables on investors’ perceptions. The findings reveal that financial knowledge and awareness play a crucial role in shaping investors’ perceptions and investment behavior. Financially literate investors tend to make rational and strategic investment decisions. Other variables, such as behavioral biases, risk perception, and social influences, were also found to significantly affect investor perception and behavior; however, their impact was less pronounced than that of knowledge and awareness. These findings provide valuable insights for investors, financial institutions, policymakers and other stakeholders in promoting a sustainable equity market in Nepal.